2020
DOI: 10.32526/ennrj.18.4.2020.39
|View full text |Cite
|
Sign up to set email alerts
|

Response of Streamflow and Soil Erosion to Climate Change and Human Activities in Nam Rom River Basin, Northwest of Vietnam

Abstract: Change in climate and land use is the main cause of increasing streamflow and soil erosion. However, very few studies have investigated these changes on a basin scale. Thus, this study used the Soil and Water Assessment Tool (SWAT) method to evaluate the effects of both land use and climate change effects on streamflow, sediment yield, and soil loss in the Nam Rom River Basin, Northwest of Vietnam. The outputs of the SWAT model demonstrated it to be a strong tool in predicting catchment hydrology, sediment tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Their results presented that increases in streamflow and sediment yield were observed in the period 1995-2005 due to conversions of forest land to crop land and urban area and reductions in streamflow and sediment load were observed during the period 2005-2010 due to reforestation [18]. Recently, Ngo and Nguyen conducted a similar study in the Nam Rom River Basin and reported that the reforestation reduced sediment yield during the period 1992-2015 [19]. In general, these studies have mainly focused on the influence of past LUC change and very few studies have conducted an inquiry into how future LUC change will affect streamflow and sediment load, which is essential for a robust understanding of the potential influences of LUC change on land and water resources in the region.…”
Section: Introductionmentioning
confidence: 95%
“…Their results presented that increases in streamflow and sediment yield were observed in the period 1995-2005 due to conversions of forest land to crop land and urban area and reductions in streamflow and sediment load were observed during the period 2005-2010 due to reforestation [18]. Recently, Ngo and Nguyen conducted a similar study in the Nam Rom River Basin and reported that the reforestation reduced sediment yield during the period 1992-2015 [19]. In general, these studies have mainly focused on the influence of past LUC change and very few studies have conducted an inquiry into how future LUC change will affect streamflow and sediment load, which is essential for a robust understanding of the potential influences of LUC change on land and water resources in the region.…”
Section: Introductionmentioning
confidence: 95%
“…Population density in the tropics is projected to increase rapidly (e.g., Laurance et al, 2014), hence >50% of the world's population is expected to reside in the tropics by 2050. Land conversion for livestock and agriculture has intensified in the tropics since the "Green Revolution" in the second half of the 20th century (e.g., Evenson and Gollin, 2003;Le Huong and Thanh Son, 2020;Sinha et al, 2020;Alavez-Vargas et al, 2021;Jankowski et al, 2021), leading to increased sediment supply to some lowland lakes. Owens (2020) describes that greater sediment accumulation rates have become a threat to water security.…”
Section: Recent Sediment Accumulation Rates Increasing In Tropical Lo...mentioning
confidence: 99%
“…In many cases, this represents an advance in the efficient use of resources. However, the unreasonable use of resources and the environment affects the process of changes in resources and the environment to varying degrees, causing or even controlling adverse gradients or mutations in resources and the environment, such as increased greenhouse gas emissions [13], river cutoff [14], and soil erosion [15]. Desertification is a more obvious example, and land and its related issues have always a racted great concern.…”
Section: Introductionmentioning
confidence: 99%